2007
DOI: 10.1038/sj.bmt.1705585
|View full text |Cite
|
Sign up to set email alerts
|

Patients at high risk for CMV infection and disease show delayed CD8+ T-cell immune recovery after allogeneic stem cell transplantation

Abstract: Human cytomegalovirus (CMV) is a major cause of death after transplantation. The frequency of pp65-specific T cells was examined in 38 HLA-A2 þ stem cell recipients during the first year after transplantation. Patients were divided into four groups based on donor/recipientand dÀ/rÀ (n ¼ 5). Peripheral blood mononuclear cells were stimulated with the CMVpp65 peptide NLVPMVATV, and the specific T-cell frequency was assessed by interferon gamma (IFN-c) ELISPOT assay. Responding T cells were characterized by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 27 publications
4
61
3
Order By: Relevance
“…CD8 þ T lymphocytes and natural killer cells have an important function in maintaining cell-mediated immunity against CMV and suppressing viral replication, 21,22 and inadequate or defective recovery of CD8 þ T cells after transplant has been shown to contribute to a higher incidence of CMV reactivation and disease in transplant recipients. [23][24][25][26][27] Though previous studies have showed similar patterns of immune reconstitution after non-myeloablative transplantation compared with myeloablative transplants, 28 the use of ATG or alemtuzumab has been shown to delay CMV-specific immune reconstitution. 8,9,10,17 In this study, the OS among patients with CMV reactivation was not significantly lower than patients without CMV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 þ T lymphocytes and natural killer cells have an important function in maintaining cell-mediated immunity against CMV and suppressing viral replication, 21,22 and inadequate or defective recovery of CD8 þ T cells after transplant has been shown to contribute to a higher incidence of CMV reactivation and disease in transplant recipients. [23][24][25][26][27] Though previous studies have showed similar patterns of immune reconstitution after non-myeloablative transplantation compared with myeloablative transplants, 28 the use of ATG or alemtuzumab has been shown to delay CMV-specific immune reconstitution. 8,9,10,17 In this study, the OS among patients with CMV reactivation was not significantly lower than patients without CMV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…64 Although a CMV-seropositive recipient is at higher risk for transplant-related mortality than a seronegative recipient, 65,66 the impact of donor serostatus on nonrelapse mortality and survival when the recipient is seropositive remains controversial. [67][68][69][70][71][72][73][74][75][76][77][78] This combination, however, has been reported as a risk factor for delayed CMV-specific immune reconstitution, [79][80][81][82] repeated CMV reactivations, 80,83 late CMV recurrence, 84 and development of CMV disease. 46,80,85 Other risk factors for CMV infection after allogeneic HSCT include the use of high-dose corticosteroids, T-cell depletion, acute and chronic GVHD, and the use of mismatched or unrelated donors.…”
Section: Allogeneic Hsct Recipientsmentioning
confidence: 99%
“…[67][68][69][70][71][72][73][74][75][76][77][78] This combination, however, has been reported as a risk factor for delayed CMV-specific immune reconstitution, 79-82 repeated CMV reactivations, 80,83 late CMV recurrence, 84 and development of CMV disease. 46,80,85 Other risk factors for CMV infection after allogeneic HSCT include the use of high-dose corticosteroids, T-cell depletion, acute and chronic GVHD, and the use of mismatched or unrelated donors. 43,46,[85][86][87][88][89] The use of sirolimus for GVHD prophylaxis seems to have a protective effect against CMV infection, possibly because of the inhibition of cellular signaling pathways that are co-opted by CMV during infection for synthesis of viral proteins.…”
mentioning
confidence: 99%
“…[34][35][36] Lack of T cell immunity against CMV is associated with an increased risk of late onset/recurrent CMV antigenemia and CMV disease. 21,[23][24][25][26][27][28][29] In EBV and ADV infections, importance of T cell immunity against was also reported. [37][38][39] Therefore, if T cell immunity is found to be insufficient in patients with viral reactivation, adoptive immunotherapy to enhance T cell reconstitution could be an option to consider in order to treat or prevent the development of endorgan disease (Fig.…”
Section: Importance Of T Cells Against Viral Infectionsmentioning
confidence: 99%
“…In terms of viral infections, it is well established that T cells play an important role. [21][22][23][24][25][26][27][28][29][30] In terms of mold infections, innate immunity alone was considered important historically in the control of mold infections. However, recent studies found that adaptive immunity, in particular Th1 cells, was relevant in the control of aspergillus infections.…”
Section: Introductionmentioning
confidence: 99%